Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Square terhadap Hasil Belajar Geografi Siswa Kelas XI di SMAN 2 Solok Selatan - Fadila Naitul Husna; Ade Irma Suryani; Loli Setriani (Departement of Mathematics Education, 2023)
This research is motivated by the lack of variety of media in learning. Students are less motivated in the teaching and learning process and there are obstacles in the delivery of learning material and are often found in learning outcomes that are < from KKM. This study aims to see the effect of using the Think Pair Square Cooperative learning model on the learning outcomes of Geography students in class XI SMAN 2 Solok Selatan. The use of the Think Pair Cooperative learning model turned out to make students more enthusiastic in responding to the model applied by the researcher. The type of research used is a quasi-experimental research type. The population in this study were students of class XI IPS at SMAN 2 Solok Selatan for the 2023/2024 academic year. Class XI IPS 1 control class, XI IPS 2 experimental class. The data analysis technique used was descriptive statistical technique and inferential statistical analysis. Based on the research results, the control class average was 79.48 and the experimental class average was 86.89. Based on the t-test conducted on the two sample class learning outcomes, the t value was 5,945 with sig 0.000 <0.005. It can be concluded that there is an influence of the think pair square Cooperative learning model on the learning outcomes of Geography class XI students at SMAN 2 Solok Selatan.